2012
DOI: 10.3126/bibechana.v8i0.4784
|View full text |Cite
|
Sign up to set email alerts
|

A non–destructive compositional analysis of thin surface films formed on W–xTa alloys by angle resolved X–ray photoelectron spectroscopy

Abstract: Synergistic effect of the simultaneous additions of tungsten and tantalum in the extremely high corrosion resistance properties of the spontaneously passivated sputter-deposited W-xTa alloys was investigated using a non−destructive angle resolved X−ray photoelectron spectroscopy (angle resolved XPS) techniques in this study. In−depth surface analyses of the thin passive films formed on the spontaneously passivated amorphous/nanocrystalline W-xTA alloys using angle resolved XPS analyses revealed that the high c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
3
6
0
Order By: Relevance
“…For corrosion and materials scientists, the AR-XPS technique becomes one of the very viable in-depth surface characterization tools to study the mechanism of very high corrosion-resistant of metals or/and alloys during the last three decades [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. It allows researchers to check out successfully the constitution of homogeneous or heterogeneous passive surface films formed on the corrosion-resistant metal or/and alloys.…”
Section: Introductionmentioning
confidence: 99%
“…For corrosion and materials scientists, the AR-XPS technique becomes one of the very viable in-depth surface characterization tools to study the mechanism of very high corrosion-resistant of metals or/and alloys during the last three decades [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. It allows researchers to check out successfully the constitution of homogeneous or heterogeneous passive surface films formed on the corrosion-resistant metal or/and alloys.…”
Section: Introductionmentioning
confidence: 99%
“…At a lower take−off angle of photoelectrons, the intensity signals (I) from the surface of sample species located in the exterior part of the surface films are enhanced. Therefore, the apparent composition of the surface films is changed with the take−off angle of photoelectrons in the ARXPS measurements (Bhattarai 2012). In recent years, this ARXPS technique was used to examine the formation of homogeneous orheterogeneous nature of the passive films formed on the corrosion−resistant alloys (Asami et al 1987;Akiyama et al 1996;Bhattarai et al b, 1998Marcus 1998;Bhattarai 1998Bhattarai , 2000.…”
Section: Introductionmentioning
confidence: 99%
“…The passivating elements such as tungsten and zirconium can generally improve corrosion resistance of alloys in aggressive environments. It has been reported that less than 10 at% (atomic percentage) of tungsten addition to sputter-deposited W-xCr alloys was enough to cause spontaneous passivation of the alloys and they showed higher corrosion resistance than those of tungsten and chromium in aggressive environments (Bhattarai et al 1998 c;Bhattarai 1998Bhattarai , 2000Basnet and Bhattarai 2010). On the other hand, zirconium is widely known for its superior corrosion resistance behavior in acidic environments, although it suffers pitting corrosion by anodic polarization.…”
Section: Introductionmentioning
confidence: 99%
“…Varieties of corrosion-resistant rapidly quenched alloys were developed in 1970's [2][3][4][5][6]. Since 1990's, it has been reported that the sputterdeposited binary tungsten-titanium [7][8][9][10], tungsten-zirconium [7,11,12], tungsten-chromium [7,13,14], tungsten-niobium [7,[15][16][17], tungsten-tantalum [7,[18][19][20], tungsten-molybdenum [21][22][23][24] and tungsten-nickel [21,25,26], and ternary tungsten-based [27][28][29][30][31][32][33] alloys showed higher corrosion resistance than those of alloy-constituting elements in different corrosive environments.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that a beneficial effect of tantalum to improve the corrosion resistance of nickel−base alloys in 12 M HCl [48]. A series of the sputter−deposited binary tantalum−containing alloys showed higher corrosion resistance than those of alloying elements due to spontaneous passivation in aggressive media [5,20,[49][50][51].…”
Section: Introductionmentioning
confidence: 99%